Power Inside the Firm and the Market: A General Equilibrium Approach - Dalia Marin; Thierry Verdier (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
Recent years have witnessed an enormous amount of reorganization of the corporate sector in the US and in Europe. This paper examines the role of market competition for this trend in corporate reorganization. We find that at intermediate levels of competition the CEO of the corporation decides to have less power inside the firm and to delegate control to lower levels of the firms' hierarchy. Thus, workers empowerment and the move to flatter firm organizations emerge as an equilibrium when competition is not too tough and not too weak. The model predicts merger waves or waves of outsourcing when countries become more integrated into the world economy as the corporate sector reorganizes in response to an increase in international competition.
urn:nbn:de:bvb:19-epub-13442-4
Keywords: F12; D23; L22; L1; 330; monopolistic competition; international trade; corporate reorganisation; flattening firm hierarchies